Engaging stakeholders to inform policy developments in early childhood education and outside school hours care - Hadley, Fay; Harrison, Linda J.; Lavina, Leanne; Barblett, Lennie; Irvine, Susan; Bobongie-Harris, Francis; Cartmel, Jennifer (Frontiers in Education, 2024)
The application of engagement strategies to ensure democracy of decisions is increasingly valued and adopted by governments to ensure trust in the process and ownership of the outcome. This paper describes the approach and methods used to engage early childhood education and care (ECEC) and outside school hours care (OSHC) stakeholders in the contemporizing and updating of Australia's national Approved Learning Frameworks (ALFs): Belonging, Being and Becoming: The Early Years Learning Framework for Australia (EYLF) and My Time Our Place: Framework for School Age Care (MTOP). Theoretical underpinnings of a robust stakeholder engagement strategy ensured a range of methods were developed to communicate with and encourage participation by the diversity of stakeholders who are invested in ECEC and OSHC in Australiabroadly defined as approved providers, teachers, educators, families, children and young people, regulatory authorities and other professionals who provide support and advice. A mixed-method, sequential 3-Stage design was developed to gather the insights, responses, and perspectives of stakeholders who provided, worked in, used, attended, or supported ECEC and/or OSHC settings. Stakeholder feedback included survey ratings and written comments, focus group and panel discussions, educator documentation and videodiaries, and the writings, talking, and drawings of children and young people. Evaluation methods focus on the number, diversity, and depth of stakeholder responses. In conclusion, we reflect on the usefulness, benefits, limitations, and effectiveness of our approach to participatory engagement to inform government policy development and decision making.